2013
DOI: 10.1111/pedi.12061
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Diabetes Consortium Type 1 Diabetes New Onset (NeOn) Study: factors associated with HbA1c levels one year after diagnosis

Abstract: Objective To identify determinants of HbA1c levels one year after the diagnosis of type 1 diabetes (T1D) in participants in the Pediatric Diabetes Consortium (PDC) T1D New Onset (NeOn) Study. Research Design and Methods Diabetes-specific as well as socioeconomic factors during the first year following diagnosis were analyzed in 857 participants (mean age 9.1 years, 51% female, 66% non-Hispanic White) not participating in an intervention study who had an HbA1c value at 12 months. Results Mean ± SD HbA1c at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
71
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 43 publications
15
71
6
Order By: Relevance
“…Of particular concern, our crosssectional data also demonstrate that higher weight in youth with T1D may be inversely associated with achieving the goals of intensive treatment, since increased BMIz was associated with higher HbA1c in both registries. This relationship between HbA1c and BMI was not found in a recent paper by Redondo et al, but that study assessed a cohort of newly diagnosed patients with T1D, whereas our report was limited to participants with at least 1 year T1D duration (mean duration 4.8±3.5 years) (28). Increased BMIz was associated with a greater risk of SH in the DPV cohort, but an association between BMI and SH was not found in the T1DX registry.…”
Section: Discussioncontrasting
confidence: 63%
“…Of particular concern, our crosssectional data also demonstrate that higher weight in youth with T1D may be inversely associated with achieving the goals of intensive treatment, since increased BMIz was associated with higher HbA1c in both registries. This relationship between HbA1c and BMI was not found in a recent paper by Redondo et al, but that study assessed a cohort of newly diagnosed patients with T1D, whereas our report was limited to participants with at least 1 year T1D duration (mean duration 4.8±3.5 years) (28). Increased BMIz was associated with a greater risk of SH in the DPV cohort, but an association between BMI and SH was not found in the T1DX registry.…”
Section: Discussioncontrasting
confidence: 63%
“…The SEARCH study revealed that, among youth with T1D, 22.1% were overweight compared with 16.1% without diabetes, and 12.6% were obese . In the Pediatric Diabetes Consortium, among 857 participants 10% were overweight and 9% obese at diagnosis . This phenomenon is not unique to the United States; it has also been reported from other parts of the world .…”
Section: Diagnosis Of T2d In Youthmentioning
confidence: 95%
“…While factors promoting the increasing prevalence of T1D are not understood, increasing rates of T2D are linked with the obesogenic environment of developed countries, nutritional excesses, and rapid increases in obesity, together with declining physical activity in high‐risk populations. Concurrently, increasing obesity among youth with T1D is clouding the clinical distinction between the two conditions . Thus, some reports of increasing rates of T2D may mistakenly characterize some obese T1D youth as having T2D.…”
Section: Epidemiology Of Youth T2dmentioning
confidence: 99%
“…This suggests that parental involvement as well as, the manner in which parents interact with their child when completing T1D management tasks may influence short‐ and long‐term glycemic control . In parents of children newly diagnosed with T1D, this balancing act is even more complicated as parents themselves are learning daily T1D self‐care while teaching their child about his or her own T1D self‐care …”
Section: Introductionmentioning
confidence: 99%